1978
DOI: 10.1055/s-0028-1129252
|View full text |Cite
|
Sign up to set email alerts
|

Psychische Aspekte der Glossodynie*

Abstract: The term glossodynia refers to all conditions with pain and dysaesthesia of the tongue and entire oral mucosa manifesting themselves in burning, prickling, itching, stinging, and other frequently bizarre sensations as well as subjective xerostomia and bad taste. In most cases psychiatric diseases are the cause of the complex of complaints whereas local and general disorders are of only minor importance. Menopausal women with atypical depression are most often affected. Schizophrenia and abnormal personality de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…They did not have any other mental disorders. Patients with BMS reportedly suffer from anxiety, hypochondriasis and depression 2–8 . Many studies suggest that psychogenic factors (including anxiety, depression, stress, life events personality disorder, and phobia of cancer) are possible causal factors 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They did not have any other mental disorders. Patients with BMS reportedly suffer from anxiety, hypochondriasis and depression 2–8 . Many studies suggest that psychogenic factors (including anxiety, depression, stress, life events personality disorder, and phobia of cancer) are possible causal factors 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with BMS reportedly suffer from anxiety, hypochondriasis and depression. [2][3][4][5][6][7][8] Many studies suggest that psychogenic factors (including anxiety, depression, stress, life events personality disorder, and phobia of cancer) are possible causal factors. 1 However, psychopathology in BMS may be a reaction to persistent pain and not a cause of the pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After organic causes such as fungal infections, Lichen ruber mucosae, prosthesis pressure pain, deficiency diseases and other rare causes such as a cerebral psychosyndrome have been ruled out [30], psychosomatic diagnostics should be equally initiated during the differential-diagnostic clarification. With respect to the premorbid personality of patients with GD, Haneke [10] reported that almost all appeared nervous or even tense, and many appeared to be anxious and introverted, depressed or even lachrymose. In diagnosed depression, an attempt at therapy over a sufficiently long time, that is at least 3 weeks, with antidepressants is indicated [12] after the patient has been convinced of the necessity of therapy [24].…”
Section: Introductionmentioning
confidence: 99%